The lived experience of nurses transitioning to professional practice during the COVID‐19 pandemic. Issue 5 (11th June 2022) - Aukerman, Ranae; White, Lynn; Gierach, Michelle; Miller, Tara; Wolles, Brenda
Abstract: As a result of the COVID‐19 pandemic, newly graduating nurses have entered into rapidly changing clinical environments, experiencing healthcare in a manner for which they were not fully prepared. The purpose of this study is to describe the lived experience of these newly graduated registered nurses (RNs) who transitioned to practice during the COVID‐19 pandemic, and to gain understanding of how to better prepare future graduates for similar situations. A multisite qualitative phenomenological design was used in this study of 12 frontline nurses that graduated in the spring of 2020 and transitioned into their new role as RNs. A trained research team conducted semistructured interviews and completed a thematic analysis of the data. The results were six themes that emerged from the study participants' interviews: (1) fear, (2) emotional conflict, (3) self‐doubt, (4) alone, (5) communication barriers, and (6) finding the positive.